2020
DOI: 10.30534/ijatcse/2020/288942020
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Android Malware using its Image Sections

Abstract: Privacy is a big concern as hackers are stealing data and misusing it by engineering malicious applications. There is a rapid increase in malware attacks like spyware, premium-rate SMS Trojans, botnets, aggressive adware, privilege escalation, and banking trojans which were distributed through the applications present on Google play store as well as unofficial application stores. Malware uses dominant techniques such as packing, encryption, a transformation of code, environment-aware approaches to evade detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Oumayma Oueslati, Ahmed Ibrahim S. Khalil, Habib Ounelli in Sentiment Analysis for Helpful Reviews Prediction suggested Gathering only the helpful reviews would reduce information processing time and save effort [16]. Priyanka Thakur and Dr. Rajiv Shrivastava in A Review on Text Based Emotion Recognition System suggested that analysis is focused on the extraction of emotions and opinions of the people towards a particular topic from a structured, semi-structured or unstructured textual data [17].…”
Section: Methodsmentioning
confidence: 99%
“…Oumayma Oueslati, Ahmed Ibrahim S. Khalil, Habib Ounelli in Sentiment Analysis for Helpful Reviews Prediction suggested Gathering only the helpful reviews would reduce information processing time and save effort [16]. Priyanka Thakur and Dr. Rajiv Shrivastava in A Review on Text Based Emotion Recognition System suggested that analysis is focused on the extraction of emotions and opinions of the people towards a particular topic from a structured, semi-structured or unstructured textual data [17].…”
Section: Methodsmentioning
confidence: 99%
“…system calls respectively. Authors in [14] utilizes the GIST features for the classification of malware families. The classifiers such as Support Vector Machines, K-Nearest Neighbor, Random Forests, and Naive Bayes were used in the experimenation.…”
Section: Related Workmentioning
confidence: 99%